Lectures in honor of the Alexander Campbell bicentennial, 1788-1988 - Campbell, Alexander, 1788-1866 (Disciples of Christ Historical Society, 1988)
In 1984, the Disciples of Christ Historical Society set forth a program to celebrate the 200th birthday of Alexander Campbell. This book launched a renewed interest in Stone-Campbell history and inspired research that shaped numerous historical projects. Contributors include T. Dwight Bozeman, Robert O. Fife, Richard L. Harrison, Samuel S. Hill, Thomas Olbricht, William J. Richardson, D. Newell Williams, Eva Jean Wrather, and Barbara Brown Zickmund.